2017 1st International Workshop on Arabic Script Analysis and Recognition (ASAR) 2017
DOI: 10.1109/asar.2017.8067754
|View full text |Cite
|
Sign up to set email alerts
|

Unconstrained scene text and video text recognition for Arabic script

Abstract: Abstract-Building robust recognizers for Arabic has always been challenging. We demonstrate the effectiveness of an end-toend trainable CNN-RNN hybrid architecture in recognizing Arabic text in videos and natural scenes. We outperform previous stateof-the-art on two publicly available video text datasets -ALIF and ACTIV. For the scene text recognition task, we introduce a new Arabic scene text dataset and establish baseline results. For scripts like Arabic, a major challenge in developing robust recognizers is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 36 publications
0
28
0
2
Order By: Relevance
“…The objective of this task is to predict precise word level bounding boxes and the corresponding script class for each word. Existing text recognition algorithms [18,19,39] are language-dependent which makes script identification a prerequisite task for the other methods. In Section 4.3, we experimentally demonstrated that script identification is not required for multi-language text recognition.…”
Section: Joint Multi-language Text Localization and Script Identificamentioning
confidence: 99%
“…The objective of this task is to predict precise word level bounding boxes and the corresponding script class for each word. Existing text recognition algorithms [18,19,39] are language-dependent which makes script identification a prerequisite task for the other methods. In Section 4.3, we experimentally demonstrated that script identification is not required for multi-language text recognition.…”
Section: Joint Multi-language Text Localization and Script Identificamentioning
confidence: 99%
“…The technique is evaluated on two datasets ACTiV [115] and the ALIF [116,117] and reports high recognition rates. A similar work is reported in [118] where a combination of CNN and LSTM is employed to recognize Arabic text in video frames. Another deep learning-based solution is presented in [119] where Lu et al compare the performance of different pre-trained ConvNets for detection and recognition of caption text.…”
Section: Text Recognitionmentioning
confidence: 92%
“…In recent years, several novel works for cursive text detection and recognition in video images have been developed [51]- [54], while a limited work is presented for cursive text recognition in natural scenes [55]- [57]. Ahmed et al [55], modified the maximally stable extremal region method to extract the scale-invariant features and passed to the multi-dimensional long short term memory (MDLSTM) classifier.…”
Section: B Cursive Text Recognition In Video and Natural Scene Imagesmentioning
confidence: 99%
“…Jain et al [51] used a hybrid CNN-RNN network to recognize Arabic text in videos and natural images. To train the network, they created a large-scale synthetic dataset.…”
Section: Ieee Accessmentioning
confidence: 99%